Orthomnion javense (Mniaceae, Bryophyta), new to India and Nepal - Omar, Ichha; Nair, M.c.; Asthana, A.k.; Asthana, Geeta (Phytotaxa, 2020)
During studies on family Mniaceae in India, plants of Orthomnion javense Koponen have been recognized which is a new record for India and East Nepal, earlier it was known from China, Indonesia, Japan, Laos, Papua New Guinea, Philippines and Vietnam. O. javense is characterized by its fragile leaves, costa ending below the leaf apex, 1–3 cells wide border extending near leaf apex. Morpho–taxonomic details of Indian plants of O. javense and paratype (NICH 2130; E. Nepal) of O. noguchii Koponen (identified as O. javense) are provided.